Determinants of Dividend Policy: U.S. Empirical Evidence - Luo, Ying (2012)
This research aims to determine the variables that affect the dividend policy for 144 United Stated firms from the year of 2002 to 2011. In particular, the study not only examines the entire sample, but also compares the individual industry samples: service and manufacturing companies to analyse the indicators of dividend policy. The dividend payout ratio is defined as dividend policy in this study. The firm characteristics used in the research to determine the dividend payout level are profitability, firm size, asset tangibility, firm leverage, asset growth, firm risk and industry type. The data sources for this study are collected from the “DataStream”, a historical financial numerical database system. Multiple regression model is used to evaluate the data and the research uses STATA to run the ordinary least squares regression to find out the relationship. Overall, this research ultimately concludes that the larger companies with more profitability, higher leverage but lower growth opportunity and risk are more able to pay higher dividends. Profitability, firms leverage and risk seem significant to explain the dividend policy for the US service companies. For the US manufacturing companies, the profitability, firm size and debt level are positively related with the dividend policy. In contrast, asset tangibility, growth opportunity and firm risk have a negative relationship with the US manufacturing dividend policy.